2017
DOI: 10.1111/ctr.13021
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation from donors with rhabdomyolysis and acute renal failure

Abstract: Rhabdomyolysis in deceased donors usually causes acute renal failure (ARF), which may be considered a contraindication for kidney transplantation. From January 2012 to December 2016, 30 kidneys from 15 deceased donors with severe rhabdomyolysis and ARF were accepted for transplantation at our center. The peak serum creatinine (SCr) kinase, myoglobin, and SCr of the these donors were 15 569±8597 U/L, 37 092±42 100 μg/L, and 422±167 μmol/L, respectively. Two donors received continuous renal replacement therapy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
2
8
0
2
Order By: Relevance
“…12 It is possible to argue that all three donors in this study had AKI for rhabdomyolysis. In a retrospective observational study carried out by Chen et al, they analyzed 30 patients diagnosed with KDIGO III AKI kidneys during rhabdomyolysis, compared to 90 patients who received standard kidneys, and they reported that there was no statistical difference in relation to creatinine and GFR at months 2, 6, 12 and 24; there was also no difference in the incidence of rejection, 13 showing good graft function in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…12 It is possible to argue that all three donors in this study had AKI for rhabdomyolysis. In a retrospective observational study carried out by Chen et al, they analyzed 30 patients diagnosed with KDIGO III AKI kidneys during rhabdomyolysis, compared to 90 patients who received standard kidneys, and they reported that there was no statistical difference in relation to creatinine and GFR at months 2, 6, 12 and 24; there was also no difference in the incidence of rejection, 13 showing good graft function in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…1 We described that kidneys from donors with significant acute kidney injury caused by rhabdomyolysis can achieve excellent graft function, even when the kidneys are anuric or discolored. 2 We ascribe the excellent outcomes we reported to the relatively young age of the donors (mean age of 24.5 years), the cause of the donors' death (12 of 15 donors died as a result of motor vehicle accidents), and the absence of chronic injury (>10% glomerulosclerosis, interstitial fibrosis, tubular atrophy, arteriolar hyalinosis, and fibrous intimal thickening) on pre-implant biopsies. The mean kidney donor risk index of the donors was 0.88 ± 0.10 (range, 0.73-1.11), which is rather good.…”
mentioning
confidence: 68%
“…Kidneys with significant myoglobin casts could show a discolored appearance (from brown to glossy black). 2 If the rhabdomyolysis donor has a peak serum creatinine kinase level higher than 20 000 U/L, and has tea-colored urine, the kidneys are likely to have a black appearance after in situ cold perfusion.…”
Section: Reply To "Correspondence To: Kidney Transplantation From Donmentioning
confidence: 99%
“…We would like to commend the authors on such an interesting and thought-provoking article. 1 The authors have described the use of organs from donors who have significant acute kidney injury with severe rhabdomyolysis. Indeed, two donors required continuous renal replacement therapy.…”
Section: Dear Editormentioning
confidence: 99%